2008
DOI: 10.1029/2008gl033905
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic triggering of high‐frequency bursts by strong motions during the 2004 Parkfield earthquake sequence

Abstract: High‐pass filtering (>20 Hz) of acceleration records from the USGS Parkfield Dense Seismograph Array (UPSAR) reveals a series of bursts that occur only during strong shaking from the 2004 Mw6 Parkfield, California, earthquake and its immediate aftershocks. Because there is no correlation between these high frequency bursts observed at closely spaced stations, we hypothesize that they are associated with dynamically triggered events occurring within 20 meters of the stations in the highly fractured shallow crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
0
34
1
Order By: Relevance
“…Second, the stress perturbation associated with the P wave is usually considered to be too small to cause much dynamic triggering at large distances. Recently, Fischer et al [2008a, 2008b] reported P wave‐triggered high‐frequency bursts in the near field during 1999 Mw 7.6 Chi‐Chi, Taiwan, earthquake and the 2004 Mw 6.0 Parkfield earthquake. They estimated a triggering threshold of ∼1 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the stress perturbation associated with the P wave is usually considered to be too small to cause much dynamic triggering at large distances. Recently, Fischer et al [2008a, 2008b] reported P wave‐triggered high‐frequency bursts in the near field during 1999 Mw 7.6 Chi‐Chi, Taiwan, earthquake and the 2004 Mw 6.0 Parkfield earthquake. They estimated a triggering threshold of ∼1 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…There is direct evidence of brittle co‐seismic failure: small earthquakes in the shallow subsurface during shaking [ Fischer et al , 2008a, 2008b; Fischer and Sammis , 2009]. The largest of these events may cause brief extreme dynamic acceleration [ Aoi et al , 2008; Sleep and Ma , 2008].…”
Section: Stresses Within Seismically Damaged Regolithmentioning
confidence: 99%
“…Also from , sudden failure of shallow rock with a large stress drop will produce brief accelerations. Small events of this type result in brief pulses that can be studied by high‐pass filtering [ Fischer et al ., , Fischer and Sammis , ]. Large events of this type are a likely cause of observed brief accelerations of greater than 1 g [ Aoi et al ., ; Sleep and Ma , ].…”
Section: Shear Waves Near the Earth's Surfacementioning
confidence: 99%